FEATURES OF THE CLINICAL PICTURE OF LOWER JAW FRACTURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The number of facial injuries has more than doubled over the past 30 years, and along with the steady increase in facial skull injuries, their structure has changed significantly due to an increase in combined and multiple fractures. Long-term forecasts indicate a further increase in the frequency of such injuries and the complication of their nature due to the growth of technical equipment in production, the increase in the number of vehicles and their speed, as well as other manifestations of urbanization.